Quality-based content delivery over the Internet - Li, Xiang (Springer, 2011)
"Quality-Based Content Delivery over the Internet mainly discusses the methodology of doing quality-based content delivery in an Internet environment. Because the network is becoming intelligent and active, more and more researchers are talking about achieving personalization and customization in Internet content delivery. As researchers are aware, by introducing intelligence into a web intermediary server, they can make the content delivery more efficient and of higher quality. Still, the detailed methodology of doing so is never illustrated fully. The most critical part will be the active content transformation model. This book gives a detailed description of the active content transformation model, and provides experiments and data to show its feasibility. Some examples of how to do efficient content transformation in active web intermediary to achieve high quality are also presented to help understand the whole process. The book is an introduction and excellent reference for researchers in the Internet content delivery area. Dr. Xiang Li is an associate professor at Shanghai Jiao Tong University and the vice director of ?National Research Lab of Content Analysis?, China; Dr. Jianhua Li is a professor at the same university and the director of the same lab.